Износ кругов из СТМ при зубошлифовании - Рябченко, C.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The problems of increasing the efficiency of grinding highly precision gearwheels of the 3–4 degree of precision using superhard material tools are discussed. The efficiency of cubic boron nitride dish grinding wheels in various bonds has been studied. Recommendations how to use cubic boron nitride wheels in gear grinding are given.